Reaproveitamento energético da água de vazão ecológica em usinas hidrelétricas - Walker Matheus Ferreira da Silva (2022)
In Brazil, the power generation matrix is mostly renewable, with emphasis on hydropower, which is responsible for approximately 65% of installed capacity. Therefore, small losses related to this source can have a significant impact on the generation capacity. This paper presents a study on the impact of the maintenance of the ecological flow in the generation of hydroelectric power plants (HPP’s) installed in Brazil from a case study of two HPPs installed in the States of the Federation that have distinct laws on the subject. In one of them, it is required to maintain ecological flows higher than 70% of Q7.10 and in the other 70% of Q95. For this purpose, an analysis of the turbined and spilled flow balance was made for both HPPs and it was obtained as a result that the generation reduction ranged between 0,25% and 2,75%, being highly influenced by parameters due to the Regulation and the existence or not of reservoirs storages. In the end, it is preliminarily concluded that the generation decrease can be considered small and that possible adjustment in load dispatching can minimize even more this loss. It is suggested that new studies involving a larger number of plants be developed and that the possibility of including rules in the load dispatch contemplating environmental requirements be considered to minimize even more this loss.